Estrogen Plus Progestin and Lung Cancer in Postmenopausal Women - Chlebowski, Rowan T. (2009)
BACKGROUND: In the post intervention period of the Women’s Health Initiative (WHI) clinical trial, estrogen plus progestin increased total cancer incidence and an adverse influence on lung cancer mortality was suggested. METHODS: We conducted post hoc analyses over the full follow-up period of the WHI randomized, placebo-controlled clinical trial evaluating daily conjugated equine estrogen (CEE, 0.625 mg) plus medroxyprogesterone acetate (MPA, 2.5 mg) influence on lung cancer incidence and mortality in 16,608 postmenopausal women. FINDINGS: After 5.6 years intervention and 2.4 years additional follow-up (mean), there were 109 lung cancers in the hormone group and 85 in the placebo group (hazard ratio (HR) 1.23, 95% confidence interval (CI), 0.92, 1.63, P=0.16). While the difference was not statistically significant, for non-small cell lung cancer a possible divergence emerged over time, with more diagnoses in the CEE plus MPA group (96 vs 72 cases, respectively, HR 1.28, 95% CI 0.94, 1.73, P=0.12) and these cancers were more commonly poorly differentiated and more commonly had distant metastasis. Deaths from lung cancer were significantly increased in the CEE plus MPA group (73 vs 40 deaths, respectively, HR 1.71, 95% CI 1.16, 2.52, P=0.01) as were deaths from non-small cell lung cancer (62 vs 31 deaths, respectively, HR 1.87, 95% CI 1.22, 2.88, P=0.004). Small cell lung cancer incidence and mortality was comparable between randomization groups. INTERPRETATION: Use of estrogen plus progestin did not increase lung cancer incidence but significantly increased deaths from lung cancer. The effect may primarily be through influence on non-small cell lung cancer outcome.